Study Method of Pile near Cohesionless Slope under Reversed Lateral Load Considering Sand Strength State and Lateral Deflection of Pile - Chong Jiang; Jing Liu; Mingke Lin (Journal of Marine Science and Engineering, 2023)
A p-y curve method of pile near cohesionless soil slope under reversed lateral load is proposed. This method takes into account the failure mode of soil around the pile under reversed lateral load and the interaction mode between pile and soil, and derives the ultimate soil resistance of the pile. Considering the change of the original stress state of soil due to the lateral deflection of the pile foundation, the influence of the relative density, the initial mean effective stress and the lateral deflection of pile foundation on the internal friction angle of the sand is evaluated to further accurately calculate the soil resistance value at each depth. The prediction results of this method are well verified by comparing with the FE results and centrifuge test results. Finally, the influence of the process of lateral deflection of pile on the strength state of soil around the pile and the bearing capacity of pile is studied.